Kinn's the medical assistant - Proctor, Deborah B. (Elsevier, 2014)
Prepare for a successful career in medical assisting! Kinn's The Medical Assistant, 12th Edition helps you learn the real-world administrative and clinical skills essential to working in the health care setting. Administrative coverage ranges from professionalism and interpersonal skills to billing and coding and electronic health records; clinical content teaches how to assist with medications, diagnostic procedures, and surgeries. And no other comprehensive medical assisting text can match its coverage of assisting with medical specialties! Written by medical assisting experts Alexandra Adams and Deborah Proctor, this classic resource also includes an Evolve companion website with practical exercises and activities, videos, and review questions for the CMA and RMA certification exams